2019
DOI: 10.1007/s12031-019-1257-9
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Insulin with a GLP1 Agonist Is Associated with Better Memory and Normal Expression of Insulin Receptor Pathway Genes in a Mouse Model of Alzheimer’s Disease

Abstract: Disruption of brain insulin signaling may explain the higher Alzheimer's disease (AD) risk among type 2 diabetic (T2D) patients. There is evidence from in vitro and human postmortem studies that combination of insulin with hypoglycemic medications is neuroprotective and associated with less amyloid aggregation. We examined the effect of 8-months intranasal administration of insulin, exenatide (a GLP-1 agonist), combination therapy (insulin+exenatide) or saline, in wild-type (WT) and an AD-like mouse model (Tg2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
0
19
1
Order By: Relevance
“…Recently, Ex4 was shown to restore spatial memory and reduce ADlike histopathology in APP/PS1 mice (Bomfim et al, 2012) and APP mice (Robinson et al, 2019). In our study, the mechanism of action of Ex4 against the AD-like features (tau, neuronal loss, Aβ, learning impairment) was not directly related to effect on the insulin signaling pathway (no modulation of insulin signaling pathway protein levels or phosphorylation, data not shown).…”
Section: Ex4 Treatmentmentioning
confidence: 44%
See 3 more Smart Citations
“…Recently, Ex4 was shown to restore spatial memory and reduce ADlike histopathology in APP/PS1 mice (Bomfim et al, 2012) and APP mice (Robinson et al, 2019). In our study, the mechanism of action of Ex4 against the AD-like features (tau, neuronal loss, Aβ, learning impairment) was not directly related to effect on the insulin signaling pathway (no modulation of insulin signaling pathway protein levels or phosphorylation, data not shown).…”
Section: Ex4 Treatmentmentioning
confidence: 44%
“…Although, this was not the case in Tg2576 AD mice. While Ex4 treatment for 8 months did not significantly impact serum insulin levels, when Ex4 was combined with intranasal insulin, there was no additive or synergistic effect on Aβ levels and learning functions in Tg2576 mice (Robinson et al, 2019).…”
Section: Ex4 Treatmentmentioning
confidence: 81%
See 2 more Smart Citations
“…A recent study demonstrated that GLP-1 has a neurotrophic effect and promotes neurotrophic processes in the brain (Mainardi et al, 2015). Robinson et al demonstrated that a mixture of GLP-1 agonists boosts memory and improves insulin action in the brain (Robinson et al, 2019). Exendin-4, a stable synthetic form of GLP-1, is commonly used clinically for diabetes treatment because GLP-1 has a short half-life (Drucker and Nauck, 2006;Heppner et al, 2015b).…”
Section: What Is Glp-1?mentioning
confidence: 99%